A Fisco-Bcos platform based accurate performance analysis model of blockchain system - Mingrui XU; Yucai YAO; Xiaorong ZHU (Dianxin kexue)
In order to solve the problems such as difficult to estimate the performance of blockchain system and determine the requirement of hardware facilities, an accurate model of blockchain TPS based on model and data was established under different network structures.Considering the network architecture, the consensus algorithm, the communication of nodes and other elements, the precise model of TPS was established based on the blockchain transaction model of Fisco-Bcos platform and a large amount of actual data fitting.Through the TPS test of the actual blockchain system, the results show that the prediction TPS model established can maintain high prediction accuracy under different network architecture.